The 14‐3‐3/SLP76 protein–protein interaction in T‐cell receptor signalling: a structural and biophysical characterization - Soini, Lorenzo; Leysen, Seppe; Davis, Jeremy; Westwood, Marta; Ottmann, Christian (FEBS letters, 2021)
The SH2 domain‐containing protein of 76 kDa, SLP76, is an important adaptor protein that coordinates a complex protein network downstream of T‐cell receptors (TCR), ultimately regulating the immune response. Upon phosphorylation on Ser376, SLP76 interacts with 14‐3‐3 adaptor proteins, which leads to its proteolytic degradation. This provides a negative feedback mechanism by which TCR signalling can be controlled. To gain insight into the 14‐3‐3/SLP76 protein–protein interaction (PPI), we have determined a high‐resolution crystal structure of a SLP76 synthetic peptide containing Ser376 with 14‐3‐3σ. We then characterized its binding to 14‐3‐3 proteins biophysically by means of fluorescence polarization and isothermal titration calorimetry. Furthermore, we generated two recombinant SLP76 protein constructs and characterized their binding to 14‐3‐3. Our work lays the foundation for drug design efforts aimed at targeting the 14‐3‐3/SLP76 interaction and, thereby, TCR signalling.